Direitos humanos: o despertar da Igreja no Brasil: Aos 50 anos da Declaração Universal da ONU - Agostini, Nilo (Revista eclesiástica brasileira, 1998)
This text describes the Progressive awakening of the Church in Brazil, chiefly Catholic, in favor of amplifying or expanding concept and practices inherent in Human Rights. From the affirmation of individual rights, it progressively goes to the defense of the rights of the poor up to concentrationaround the notion ofthe “construction of citizenship". Today, one adds the necessity of a “gender perspective”. A “new evangelization" incorporates Human Rights as an integral part or even exigency of the evangelizing mission of the Church. Today this leads us to the questioning of the present structure of prevailing inequality. Corning up to the new millennium, the theme of Human Rights ressurges, giving out into ‘civil rights', 'social rights', and ‘economic rights’.